2022
DOI: 10.1049/smt2.12121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of volume and surface conductivity on the transient surface charge characteristics of DC‐GIL insulator under thermal–electric coupled fields

Abstract: Here, the transient surface charge distribution of a basin-type insulator is investigated under thermal-electric coupled fields. Horizontally installed ±200 kV direct current gasinsulated transmission lines (DC-GIL) are employed, and a 3D geometric model is applied. An improved method is introduced in the transient simulation under coupled fields, which involves simplifying geometric model, decoupling calculation, applying weak form partial differential equation, and simplifying ion transport equation. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The results indicated that both the volume and surface conductivities showed obvious influence on the surface charge distribution. It involves the transition of dominative conduction between bulk and interface conductions in charge accumulation process when varying the conductivity [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that both the volume and surface conductivities showed obvious influence on the surface charge distribution. It involves the transition of dominative conduction between bulk and interface conductions in charge accumulation process when varying the conductivity [13].…”
Section: Introductionmentioning
confidence: 99%